Elected leadership And the Sustainability of Community Satisfaction: A Field Study in Baqubah City - Al-Anbaki, Hussain (Al-Adab Journal, 2025)
The current research aims to identify the nature of the sustainability of community satisfaction, and to know the factors (building/erosion) of community satisfaction towards elected leaders, in addition to knowing the general level of community satisfaction with the performance of elected leaders, and knowing the statistically significant moral differences between the arithmetic and hypothetical means on the scale of sustainability of community satisfaction with elected leaders according to the variables (gender, age), The current research is one of the descriptive analytical researches that adopted the social survey method using the sample method, as the intentional sample was adopted in calculating the sample size from the research community represented by three residential neighborhoods in the center of Baqubah city, and the simple random sample was adopted in a cross-sectional manner in distributing the forms for the scale (sustainability of community satisfaction with elected leaders), which the researcher prepared from (24) paragraphs, after subjecting them to the necessary statistical tests to verify their ability to measure what was set For this, the research reached several results, including: There are statistically significant differences between the arithmetic means of the measure of sustainability of community satisfaction with elected leaders according to the variables (gender and age), and that general community satisfaction with the performance of elected leaders appeared at an average level, and that some elected leaders do not believe in freedom of opinion and do not accept constructive and purposeful criticism to improve the community reality, and that achieving sustainability of community satisfaction with the performance of elected leaders is linked to their interest in realistic community policies to reduce the manifestations of poverty and unemployment in society, and requires improving the educational, health and economic reality of society, and that society evaluates the performance of elected leaders through their efforts to improve the quality of life of community members, and the research reached the construction of a proposed vision from the perspective of the method of organizing society to achieve sustainability of community satisfaction towards elected leaders.